Saprochaete capitata oropharyngeal infection in a neutropenic patient: unusual presentation - Belaouni Mourad; Elbahraouy Rabii; Malki Elhoucine; Louzi Lhoussain; Er-rami Mohammed (EDP Sciences, 2020)
Introduction: Saprochete capitata is unusual etiologic agent in immunocompromised patients, particularly in those with hematologic malignancy and severe neutropenia. Most often, infections of the oral cavity are manifested clinically as oral candidiasis. Invasive forms are rarely described. Observation: a 63-year-old man consulted for pseudomembranous lesions associated with ulcero perforating lesion of the tongue and palatal region ulcerations. All evolving in a context of profound physical deterioration and severe neutropenia. Mycological examination showed Saprochaete capitata. The evolution was favorable with oral voriconazole. Comment: Saprochaete capitata invasive fungal infections have become an important cause of morbidity and mortality, particularly in hematology-oncology patients. Invasive or non-invasive, oropharyngeal involvement with this pathogen should not be underestimated in the neutropenic patient. They are the main starting point for fongemia of this pathogen, which is often fatal. Conclusion: Saprochete capitata is now recognized emerging etiologic agent in patients with hematological malignancy and severe neutropenia. Early detection and diagnosis of these fungal infections could lead to reduced morbidity and mortality, particularly in locally invasive infection.